2019
DOI: 10.3389/fendo.2019.00826
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hypothyroid Patients With L-Thyroxine (L-T4) Plus Triiodothyronine Sulfate (T3S). A Phase II, Open-Label, Single Center, Parallel Groups Study on Therapeutic Efficacy and Tolerability

Abstract: Sodium salt of levothyroxine (L-T4) is the treatment of choice of hypothyroidism. Yet, L-T4 monotherapy produces supoptimal 3,5,3′-triiodothyronine (T3)/T4 ratio in serum, as compared to normal subjects, and a minority of hypothyroid individuals on L-T4 complain for an incomplete well-being. Orally administered 3,5,3′-triiodothyronine sulfate (T3S) can be converted to T3 in humans, resulting in steady-state serum T3 concentrations for up to 48 h. In this study (EudraCT number 2010-018663-42), 36 thyroidectomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…For the reasons already given, it is argued that to both monitor T3 dosing and use TSH as a reliable measure of appropriate dosing, a slow-release T3 preparation is required and should be the goal of future trials. Recently, Santini et al [81] demonstrated using T3 sulfate as a slow-release preparation that combination T4/T3 therapy could restore a near-normal fT3:fT4 ratio with reference range TSH levels. Hence, to optimize the pharmacodynamics of LT4/LT3, it is, therefore, proposed that the target for titration in future trials should be to achieve a physiological fT3:fT4 ratio (mean = 0.32, interquartile range 0.27–0.37) in the presence of physiological TSH levels (e.g., 1.4 mU/L).…”
Section: Results: Topics Summaries Summary Statements and Consensusmentioning
confidence: 99%
“…For the reasons already given, it is argued that to both monitor T3 dosing and use TSH as a reliable measure of appropriate dosing, a slow-release T3 preparation is required and should be the goal of future trials. Recently, Santini et al [81] demonstrated using T3 sulfate as a slow-release preparation that combination T4/T3 therapy could restore a near-normal fT3:fT4 ratio with reference range TSH levels. Hence, to optimize the pharmacodynamics of LT4/LT3, it is, therefore, proposed that the target for titration in future trials should be to achieve a physiological fT3:fT4 ratio (mean = 0.32, interquartile range 0.27–0.37) in the presence of physiological TSH levels (e.g., 1.4 mU/L).…”
Section: Results: Topics Summaries Summary Statements and Consensusmentioning
confidence: 99%
“…Of the 14 combination therapy trials that have been completed, 10 employed once-daily LT3 administration (23,46,47,49,51,52,59,71,78,79), 4 employed twice-daily LT3 therapy (17,48,53,60), and none used three times a day LT3 therapy. Assuming that three times daily LT3 administration is too onerous to be used in future trials (75,76), and considering that a sustained-release preparation is not yet available for clinical use (80)(81)(82)(83), twice a day therapy may be the most reasonable option. Given that twice-daily LT3 therapy, although not ideal with respect to the T3 fluctuations produced, is likely to be the best compromise, modeling studies provide information about potential twice-daily LT3 doses that could be utilized (67,77).…”
Section: Summary Statementsmentioning
confidence: 99%
“…For the reasons already given, it is argued that to both monitor T3 dosing and use TSH as a reliable measure of appropriate dosing, a slow-release T3 preparation is required and should be the goal of future trials. Recently Santini et al demonstrated using T3 sulfate as a slow-release preparation that combination T4/T3 therapy could restore a near-normal fT3:fT4 ratio with reference range TSH levels (81). Hence, to optimize the pharmacodynamics of LT4/LT3, it is, therefore, proposed that the target for titration in future trials should be to achieve a physiological fT3:fT4 ratio (mean = 0.32, interquartile range 0.27-0.37) in the presence of physiological TSH levels (e.g., 1.4 mU/L).…”
Section: Summary Statementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even more surprisingly, no adverse events were observed. In 2019, a phase II, open-label, uncontrolled, parallel trial investigating the efficacy and safety of T3S plus T4 was conducted in 36 thyroidectomized individuals ( 178 ). A decreased T4/T3 ratio with no reduction in T3 levels was observed compared with LT4 monotherapy.…”
Section: Novel Drug Delivery Formulationsmentioning
confidence: 99%